A Clear Tool Path optimization for Rough Pocket Machining with Contour-Parallel Offset Toolpaths - Bahloul, Elhachemi; Batache, Djamel (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The context of this study is the rough machining of pockets using Contour-Parallel Offset (CPO) trajectories. This requires either minimizing the toolpath or increasing the feed rate because the objective during the roughing stage is to minimize machining time. Increasing the spacing between contours to a value close to the tool diameter minimizes the total toolpath length. However, this can result in material leftover between passes in the corners. A lot of work has been done to eliminate uncut areas after machining. Rounded loops added to the continuous CPOs proposed by several researchers and integrated into the CAM software (Mastercam) provide the most reliable solution that can maintain the feed rate at its maximum value during direction changes. However, the size of these loops penalizes the gain already achieved by maintaining the feed rate. Therefore, it is evident to conduct a detailed study to make the latter more optimized. In this paper, we propose a generalized algorithm for any polygon. It utilizes new formulas and adds an optimized loop at any point where uncut areas appear. This loop challenges the best existing methods aimed at minimizing machining time during rough pocket machining with CPO toolpaths, as it is designed in a highly optimized manner and ensures overlap in the corners between passes in any situation. For the validation of this new method, comparisons were made with the best methods found in the literature through simulations. Additionally, several tests conducted within Mastercam and with other methods, as well as a real implementation, have confirmed the effectiveness and advantage of the proposed method compared to the best existing rough pocket machining methods. The fact that this method offers a highly optimized toolpath and maintains the actual feed rate at its maximum due to the rounded profile of the loop suggests that rough pocket machining with CPO toolpaths could become the best solution.